2007
DOI: 10.1183/09031936.00091407
|View full text |Cite
|
Sign up to set email alerts
|

Reference equations for lung function screening of healthy never-smoking adults aged 18–80 years

Abstract: The need for updated spirometric reference values to be used on European populations is widely acknowledged, especially for subjects aged .70 yrs. Their reference values are generally based on extrapolations. The aim of the present study was to calculate reference values for lung function screening of healthy, never-smoking adults aged 18-80 yrs and to compare them with the most widely used reference equations.Results of screening spirometry of 8,684 healthy, never-smoking adults were used to calculate mean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 36 publications
14
102
1
10
Order By: Relevance
“…For example, it has been shown that the commonly used equations proposed by the European Respiratory Society/ European Community of Coal and Steel [15] underestimate the FEV1 compared to other reference equations [16]; as a result, these equations would classify as ''normal'' people that would be classified as having a reduction of pulmonary function using other equations. Another problem with the use of reference equations is that the coefficient of variation is age-dependent, and in adults increases considerably with age [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that the commonly used equations proposed by the European Respiratory Society/ European Community of Coal and Steel [15] underestimate the FEV1 compared to other reference equations [16]; as a result, these equations would classify as ''normal'' people that would be classified as having a reduction of pulmonary function using other equations. Another problem with the use of reference equations is that the coefficient of variation is age-dependent, and in adults increases considerably with age [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, the abundance of unrelated studies can introduce new complexities, not least because most are not generalisable to any other population than the one in which they were collected. Two exceptions to this were the Health Survey for England [32], which studied a large population (6,053 individuals) and included subjects from 16-90 yrs [31], and the recently published study by KUSTER et al [35] which was also based on a very large sample (8, predicted values as well as bias, particularly in elderly subjects who tend to overestimate their current height. Both of these studies were limited to older subjects, thereby excluding the complexities of puberty and growth spurts.…”
Section: What Is New?mentioning
confidence: 99%
“…There is a relative lack of reference data for elderly subjects [35], with existing data based on relatively small and unrepresentative samples. Most of the currently recommended reference equations were developed in the 1980s and 1990s such that the older participants would be those born at the beginning of the 20th Century, with potential for cohort effects due to changes in health, nutrition and measurement standards [44].…”
Section: Outstanding Issues Elderly Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…the prediction equations for Caucasian adult males and females derived from the Third US National Health and Nutrition Examination Survey (NHANES-III) (Hankinson et al, 1999) Brändli et al have published reference values of a Swiss population (Brädli et al, 1996;Brädli et al, 2000). In 2001 Langhammer et al published forced spirometry reference values for Norwegian adults (Langhammar et al, 2001) Recently Kuster et al published another set of reference equations for lung function of never smoking Swiss adults aged 18-80 years (Kuster et al, 2008). Falaschetti et al have published reference values predicted for an English adult population using data from the 1995/1996 Health Survey for England (Falaschetti et al, 2004).…”
Section: Diagnosis Of Chronic Obstructive Pulmonary Disease With Specmentioning
confidence: 99%